The Religious Cognition: A Meta-Analysis Study of Indonesian Students' Religious Learning Achievement - mistiani, wiwin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
The large number of published studies related to religious learning achievement in the cognitive domain certainly raises questions in the minds of research users, especially if the conclusions produced vary from one study to another. Therefore, to find out the average of students' religious learning achievement in Indonesia on the cognitive aspect, it is necessary to carry out a meta-analysis. The meta-analysis in this study aims to determine the average effect size of the aggregate Islamic learning achievement of students in Indonesia. This research uses a quantitative approach using meta-analysis. Research data was collected from various studies including journal articles, theses and student theses from 2009-2023 which were obtained through internet searches using the keyword Islamic learning achievement. The results of the research show that the average Islamic learning achievement of Indonesian students is 83.00 with a standard error of the weighted random model of 1.526 with a combined average score of 80.05 and an upper limit of 85.95. This shows that the ability/achievement in learning the Islamic religion of Indonesian students at the elementary to middle school levels has exceeded the minimum completeness, namely 75. Based on the Regression Method and Trim and Fill analysis, it was found that there was no publication bias. So the conclusions made based on the random effect model regarding the average cognitive abilities of students are valid.